Deprivation and inclusive development - Diwakar, D. M., 1956-; Mishra, G. P.; National Seminar on'Deprivation and Inclusive Development : Options and Strategies for Uttar Pradesh' (2004? : Giri Institute of Development Studies) (Lucknow : Giri Institute of Development Studies, 2006)
Contributed articles presented at the National Seminar on'Deprivation and Inclusive Development : Options and Strategies for Uttar Pradesh' held at Giri Institute of Development Studies in 2004
Includes statistical tables
Includes bibliographical references and index
Keywords: Economic indicators -- India -- Uttar Pradesh -- Congresses; Social indicators -- India -- Uttar Pradesh -- Congresses; Uttar Pradesh (India) -- Economic policy -- Congresses; Uttar Pradesh (India) -- Social policy -- Congresses